1990
DOI: 10.1099/00221287-136-9-1887
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of anthracydines: enzymic conversion of aklanonic acid to aklavinone and  -rhodomycinone by anthracycline-producing streptomycetes

Abstract: Aklanonic acid, a substituted anthraquinone, is the earliest stable intermediate isolated so far in the biosynthesis of anthracycline antibiotics. Desalted, soluble cell extracts of Streptomyces sp. C5 and Streptomyces peucetius (ATCC 29050) converted aklanonic acid to E-rhodomycinone in an S-adenosyl-L-methionine-and NADPHdependent sequence of reactions. Aklanonic acid was methylated to form aklanonic acid methyl ester (AAME), which was cyclized to form aklaviketone. Aklaviketone was reduced to aklavinone by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0
5

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 27 publications
3
66
0
5
Order By: Relevance
“…The extract feeding experiments indicated that maggiemycin produced by the dauE mutants is not converted to glycosides, even though the dauE mutant could convert intermediates excreted by other, later mutants, to glycosides. These data, along with experiments showing that maggiemycin cannot be converted to erhodomycinone in vitro (Connors et al, 1990a), demonstrate that maggiemycin is a shunt product of dauE mutants blocked in daunomycin production, rather than an intermediate in the biosynthesis pathway (Fig. 2).…”
Section: Extract Feeding Experiments To Establish a Biosynthetic Sequmentioning
confidence: 86%
See 4 more Smart Citations
“…The extract feeding experiments indicated that maggiemycin produced by the dauE mutants is not converted to glycosides, even though the dauE mutant could convert intermediates excreted by other, later mutants, to glycosides. These data, along with experiments showing that maggiemycin cannot be converted to erhodomycinone in vitro (Connors et al, 1990a), demonstrate that maggiemycin is a shunt product of dauE mutants blocked in daunomycin production, rather than an intermediate in the biosynthesis pathway (Fig. 2).…”
Section: Extract Feeding Experiments To Establish a Biosynthetic Sequmentioning
confidence: 86%
“…According to the hypothesis proposed by Eckardt & Wagner (1 988), maggiemycin-accumulating strains are deficient in their ability to convert aklaviketone to aklavinone, which is the normal C-11 hydroxylase substrate. In the absence of the aklavinone reductase, aklaviketone accumulates and is apparently hydroxylated at C-1 1 to produce maggiemycin (Connors et al, 1990a). The extract feeding experiments indicated that maggiemycin produced by the dauE mutants is not converted to glycosides, even though the dauE mutant could convert intermediates excreted by other, later mutants, to glycosides.…”
Section: Extract Feeding Experiments To Establish a Biosynthetic Sequmentioning
confidence: 92%
See 3 more Smart Citations